The morphological development of Square Victoria in Montreal - Youssef, Karim (Urban development and infrastructure, 2022)
"Are the criteria by which to judge the validity of new interventions in the urban planning and the urban design of our cities, open spaces, and squares to be based on the historical morphological development of the place? Or is history just a tool by which we justify our interventions so that we may regulate the pace of the inevitable change of the form of our urban places to conserve the urban identity of the place and thereby the social and cultural identity of its inhabitants? The book traces the urban morphological development of Square Victoria in Montreal since its inception as a market-square and assesses the recent reconstruction of Square Victoria considering its historical evolution. The book follows a socio-economic approach for the study of the downtown urban square. The urban morphological development of Square Victoria is divided into three major phases: the pre-industrial, the industrial, and the post-industrial. The development of Square Victoria is examined in relation to the larger context of socio-economic transformations of the city of Montreal. The market-square undergoes a double mutation. The first mutation was due to the Industrial Revolution during which the square was renamed Square Victoria and the hay market was transferred to another location in the city (in St. Ann's Ward). It was during the Industrial Age that Square Victoria attains its mature form in the years 1930s in two steps; first Square Victoria becomes the commercial downtown city-center and then becomes part of the business city-center. The second mutation of Square Victoria was due to the Informational Technology Revolution and the new principles of modern urbanism. The urban development of the square suffered from this mutation with the direct result of the loss of the quality of enclosure and character of the square. Architects Daouste Lestage and Provencher Roy judiciously decided to retrieve the identity of the square by designing their interventions in conformity with the historical evolution of the square, especially retrieving its outstanding qualities characterizing it at its maturity in the 1930s"--